Odpowiedź :
Odpowiedź:
[tex]1.\\\\a)\ \ 0,8y\cdot4t\cdot2y=1,6y^2\cdot4t=6,4y^2t=6,4ty^2\\\\\\b)\ \ \dfrac{0,75ab\cdot(-b)}{\frac{1}{4}}=\dfrac{-\not0,75^3ab^2}{\not0,25_{1}}=\dfrac{-3ab^2}{1}=-3ab^2\\\\\\c)\ \ 2x^2-xy^2-5x^2+2xy^2=2x^2-5x^2-xy^2+2xy^2=-3x^2+xy^2\\\\\\d)\ \ (d^4-1)(d+1)=d^4\cdot d+d^4-d-1=d^5+d^4-d-1\\\\\\e)\ \ x(x+1)(x+2)=(x^2+x)(x+2)=x^3+2x^2+x^2+2x=x^3+3x^2+2x\\\\\\f)\ \ (x+2)(x^2-3x+1)=x^3-3x^2+x+2x^2-6x+2=x^3-x^2-5x+2[/tex]
[tex]2.\\\\(y^2+1)-(y^2-y)+15=y^2+1-y^2+y+15=16+y\\\\dla\ \ y=3,6\\\\16+y=16+3,6=19,6[/tex]